Ethanolic rhizome extract from Kaempferia parviflora Wall. ex. Baker Induces apoptosis in HL-60 cells - Banjerdpongchai R. (2014)
Kaempferia parviflora Wall. ex. Baker is a Thai herb containing many flavonoids that have anti-inflammatory, anti-allergic and antioxidant activities. The objective of this study was to demonstrate apoptotic effects of Kaempferia parviflora Wall. ex. Baker rhizome ethanolic extract on HL-60 cells in vitro. The extract suppressed HL-60 cell growth and decreased cell viability in a dose- and time-dependent manner. Apoptotic cell death was demonstrated by changes in cell morphology, externalization of phosphatidylserine on the cell surface, loss in mitochondrial transmembrane potential and activation of caspase 3. Apoptosis induced by K. parviflora Wall. ex. Baker rhizome ethanolic extract was enhanced by treatment with paclitaxel or doxorubicin, and inhibitors of Akt, PI3-K and MEK.